2016
DOI: 10.1021/acs.joc.6b02535
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of the Bis-silyl Ether of (+)-15-epi-Aetheramide A

Abstract: Synthesis of the macrolactone depsipeptide aetheramide A was attempted by three different approaches. The first approach to form the macrolactone involving macrolactonization to form the C1-C21 bond and the second approach using a ring-closing metathesis (RCM) strategy to form the C10-C11 olefinic bond failed. The third approach starting from R-mandelic acid, involving the RCM reaction to install the C18-C19 ring junction, was successful in assembling the macrolactone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Remarkably, once again, the presence of unprotected functionalities was well tolerated under these ruthenium-catalyzed reaction conditions, thus underscoring the mildness and efficiency of these reactions in a complex setting. From (He, 2017) [74] O [75] (49%)…”
Section: Syn Thesismentioning
confidence: 99%
“…Remarkably, once again, the presence of unprotected functionalities was well tolerated under these ruthenium-catalyzed reaction conditions, thus underscoring the mildness and efficiency of these reactions in a complex setting. From (He, 2017) [74] O [75] (49%)…”
Section: Syn Thesismentioning
confidence: 99%
“…Still, in 2016 He et al reported the preparation of aetheramides A and B by using a different strategy (15 steps, 4.7 % overall yield) . Three different approaches were also tested in the synthesis of the protected aetheramide by Revu and Prasad in 2017 . The total synthesis of aetheramide A was also accomplished by Kalesse et al in 2016 (18 steps, 0.24 % overall yield).…”
Section: Introductionmentioning
confidence: 99%
“…[7] Three different approaches were also tested in the synthesis of the protected aetheramide by Revu and Prasad in 2017. [8] The total vanced chiral building blocks: (R,R)-and (R,S)-vinylboronates and an (R)-iodoalkene. The former was prepared from (R)mandelic acid, and the latter was prepared by enantioselective allylation of 3-iodoacrylaldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Liu finished the synthesis of nannocystin Ax. Continuing our interest in natural products with medicinal potential, we pursued the total synthesis of nannocystin A, and successfully developed a concise and efficient asymmetric synthetic strategy.…”
mentioning
confidence: 99%